Prenatal diagnosis of mosaicism for trisomy 12 in a single colony at amniocentesis in a pregnancy with a favorable outcome - Chih-Ping Chen; Chao-Yun Wu; Schu-Rern Chern; Shin-Wen Chen; Fang-Tzu Wu; Wen-Lin Chen; Yun-Yi Chen; Wayseen Wang (Elsevier, 2020)
Objective: We present prenatal diagnosis of mosaicism for trisomy 12 in a single colony at amniocentesis with a favorable outcome. Case report: A 36-year-old woman underwent amniocentesis at 18 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 47,XY,+12[1]/46,XY[14]. In 15 colonies of cultured amniocytes, all three cells in one colony had the karyotype of 47,XY,+12, while the rest 14 colonies had the karyotype of 46,XY. The parental karyotypes were normal. Prenatal ultrasound findings were unremarkable. Polymorphic DNA marker analysis using the DNAs extracted from cultured amniocytes and parental bloods excluded uniparental disomy (UPD) 12. At 37 weeks of gestation, a healthy 2,828-g male baby was delivered with no phenotypic abnormality. The cord blood had a karyotype of 46,XY in 40/40 lymphocytes. Postnatal interphase fluorescence in situ hybridization (FISH) analysis on buccal cells and urinary cells revealed normal signals in 72/72 buccal cells, and trisomy 12 signals in 1/47 (2.1%) urinary cells compared with 0% (0/75 cells) of trisomy 12 signals in the normal control. Conclusion: Mosaicism for trisomy 12 in a single colony at amniocentesis without UPD 12 and fetal ultrasound abnormalities can be associated with a favorable outcome.